2006
DOI: 10.1016/j.regpep.2006.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin is expressed throughout the human gastrointestinal tract

Abstract: Background/Aim: Several studies have described that oxytocin exerts stimulatory or

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
90
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(95 citation statements)
references
References 26 publications
3
90
0
2
Order By: Relevance
“…The unique Met-enkephalin (OGF)-induced functions have led to the proposal that Met-enkephalin (OGF) may best be considered to be one of the cytokines of the immune system [27] . As our biopsies have been used for immunohistochemical analyses [28] , we have seen that there is very sparse expression of immune cells in the various tissues, which excludes the possibility that the proenkephalin-A mRNA expression observed in this study may originate from immune cells.…”
Section: Discussionmentioning
confidence: 81%
“…The unique Met-enkephalin (OGF)-induced functions have led to the proposal that Met-enkephalin (OGF) may best be considered to be one of the cytokines of the immune system [27] . As our biopsies have been used for immunohistochemical analyses [28] , we have seen that there is very sparse expression of immune cells in the various tissues, which excludes the possibility that the proenkephalin-A mRNA expression observed in this study may originate from immune cells.…”
Section: Discussionmentioning
confidence: 81%
“…Plasma ghrelin levels are under the control of both cholinergic and adrenergic fibers (Hosoda & Kangawa 2008). Peripherally administered OXT can bind to specific receptors distributed in several organs and throughout the gastrointestinal tract (Gimpl & Fahrenholz 2001, Ohlsson et al 2006. Nevertheless, there are no studies investigating the localization of the OXT receptor in ghrelin-secreting cells of the gastric mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 20 years, preclinical studies have revealed a role for OT in gut function. OT is expressed in the myenteric and submucousal ganglia and nerve fibres along the entire human GI tract (Ohlsson, Truedsson, Djerf, & Sundler, 2006). The role for OT, however, in the physiology and pathophysiology of the bowel has been largely unexplored.…”
Section: Visceral Oxytocin and Emotional Behaviormentioning
confidence: 99%